The Job Embeddedness Nomological Network in Hospitality: A Meta-analysis of Antecedents, Consequences, and Boundary Conditions - Qiu, Liqin (Auckland University of Technology, 2026)
Job embeddedness (JE) has become a central framework for understanding employee retention in the hospitality industry, yet existing findings remain fragmented across diverse contexts, workforce profiles, and measurement approaches. This master’s thesis conducts the first systematic and quantitative synthesis of JE research within hospitality, clarifying how embeddedness develops, what consequences it predicts, and under which conditions its effects vary. Drawing on 109 empirical studies comprising 112 independent samples and 40,167 employees across 23 countries, this meta-analysis integrates a wide range of antecedents, consequences, and moderators to map JE’s nomological network. Methodologically, this thesis applies psychometric meta-analytic procedures, including reliability corrections, subgroup analyses, and meta-regression. Sensitivity analyses confirmed the robustness of the synthesised effects. The results show that organisational factors - including organisational support, distributive justice, and high-performance work practices - exert the strongest influence on JE, followed by leadership behaviours and job-related characteristics such as coworker support and workplace friendship. Individual differences (e.g., age, gender, education) demonstrated only weak effects. JE was positively associated with key attitudinal and behavioural consequences, including job satisfaction, work engagement, life satisfaction, in-role and extra-role performance, and innovative behaviour, while showing moderate negative links with turnover intention and quiet quitting. Substantial heterogeneity across studies necessitated moderator analyses. Results indicated that culture and tenure moderated antecedent-JE relationships; for instance, the tenure-JE association was significantly stronger in Western and more individualistic cultures. In contrast, gender composition moderated JE-outcome relationships; for example, the JE-citizenship behaviour link was slightly stronger in samples with higherproportions of male employees. Measurement scale also shaped observed effects: multidimensional JE measures produced stronger correlations with structural and relational antecedents, whereas the global scale yielded weaker associations. This thesis advances hospitality scholarship by offering the most comprehensive empirical map of JE to date, resolving inconsistencies in prior research, and identifying meaningful directions for future empirical work. Beyond highlighting the need for longitudinal and multilevel designs, the thesis points to understudied antecedents (e.g., prosocial motivation, technological adaptation), potential nonlinear effects, and the importance of exploring the “double-edged sword” nature of JE. Practical implications for hospitality managers emphasise strengthening organisational support systems, fairness, relational climates, and purpose-driven HR practices to enhance long-term workforce sustainability.